2019
DOI: 10.1590/1678-9199-jvatitd-1471-18
|View full text |Cite
|
Sign up to set email alerts
|

Functional and biological insights of rCollinein-1, a recombinant serine protease from Crotalus durissus collilineatus

Abstract: Background: The prevalent class of snake venom serine proteases (SVSP) in Viperidae venoms is the thrombin-like enzymes, which, similarly to human thrombin, convert fibrinogen into insoluble fibrin monomers. However, thrombin-like serine proteases differ from thrombin by being unable to activate factor XIII, thus leading to the formation of loose clots and fibrinogen consumption. We report the functional and biological characterization of a recombinant thrombin-like serine protease from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…Boldrini-França et al (2015) reported the heterologous expression of an SVSP named collinein-1 from the venom of Crotalus durissus collilineatus in Pichia pastoris (methyltropic yeast) that resulted in the production of 56 mg/L of recombinant collinein-1 (rCollinein-1), and importantly, retained its functional integrity to hydrolyze bovine fibrinogen. A subsequent study has shown that rCollinein-1 may have therapeutic potential in preventing thrombus formation [149] . An acute and repeated dose (28 days) toxicity study of a recombinant thrombin-like defibrinogenating enzyme, batroxobin expressed in Pichia pastoris , showed no adverse effects at a dose of 2.5 NIH u/kg in rats and 1 NIH u/kg in dogs, indicating clinical potential in the treatment of hemostatic disturbances [150] .…”
Section: Strategies For Augmenting the Therapeutic Application And Commercialization Of Antithrombotic Proteins And Peptides Derived Frommentioning
confidence: 99%
“…Boldrini-França et al (2015) reported the heterologous expression of an SVSP named collinein-1 from the venom of Crotalus durissus collilineatus in Pichia pastoris (methyltropic yeast) that resulted in the production of 56 mg/L of recombinant collinein-1 (rCollinein-1), and importantly, retained its functional integrity to hydrolyze bovine fibrinogen. A subsequent study has shown that rCollinein-1 may have therapeutic potential in preventing thrombus formation [149] . An acute and repeated dose (28 days) toxicity study of a recombinant thrombin-like defibrinogenating enzyme, batroxobin expressed in Pichia pastoris , showed no adverse effects at a dose of 2.5 NIH u/kg in rats and 1 NIH u/kg in dogs, indicating clinical potential in the treatment of hemostatic disturbances [150] .…”
Section: Strategies For Augmenting the Therapeutic Application And Commercialization Of Antithrombotic Proteins And Peptides Derived Frommentioning
confidence: 99%
“…Recently, collinein-1, a SVSP from Crotalus durissus collilineatus venom ( Boldrini-França et al., 2015 ) was recombinantly expressed in Pichia pastoris system ( Boldrini-Franca et al., 2019 ) and demonstrated to block, independently from its catalytic activity, the hEAG1 ion channel, which is overexpressed in several cell cancer lines. Collinein-1 reduced the viability of human breast cancer cell line MCF7, which displays high expression of hEAG1, but does not affect the HepG2 and MCF10A cell lines, which present low expression of this ion channel, demonstrating that the reduction of cell viability might be connected with hEAG1 inhibition by this protein ( Boldrini-França et al., 2020 ).…”
Section: Promising Animal Toxins In Preclinical Stage and Clinical Trmentioning
confidence: 99%
“…Collinein-1 is a 29.5 kDa thrombin-like serine protease isoform from C. d. collilineatus venom that cleaves preferentially the Aα chain of fibrinogen 23 . The recombinant form of collinein-1 (rCollinein-1) was previously produced with functional integrity, using the Pichia pastoris heterologous expression system 23,24 . The screening of collinein-1 activity on voltage-gated ion channels was performed with rCollinein-1 (5 μM) on different isoforms of voltage-gated potassium (Kv) and sodium (Nav) channels expressed in Xenopus laevis oocytes.…”
Section: Collinein-1 Blocks Heag1 Channels By a Catalytic Triad-indepmentioning
confidence: 99%
“…-1 (rCollinein-1). Recombinant collinein-1 was produced as described by Boldrini-França et al 24 . Pichia pastoris cells, transformed with the recombinant plasmid (containing collinein-1 coding sequence), was pre-inoculated with 10 mL of BMGY medium (1% yeast extract, 2% peptone, 1.34% YNB, 4 × 10 −5 M biotin, 1% glycerol, 100 mM phosphate potassium pH 6.0) and incubated at 30 °C under constant stirring of 200 rpm.…”
Section: Collinein-1 Blocks Heag1 With Higher Efficiency As Compared mentioning
confidence: 99%